Impact of Digital Transformation on Organizational Resilience: A Study of SMEs in Emerging Markets - Nana Osei-Bonsu (Journal of Management Research, 2025)
Digital transformation has emerged as a critical enabler of organizational resilience, particularly for small and medium-sized enterprises (SMEs) in emerging markets. This study investigates how digital technologies, such as cloud computing, artificial intelligence (AI), and e-commerce platforms, enhance the resilience of SMEs by improving operational efficiency, adaptability, and crisis management capabilities. Using a mixed-methods approach, the research analyzes data from 300 SMEs across three emerging markets: India, Brazil, and South Africa. The findings reveal that digital transformation significantly strengthens organizational resilience by enabling SMEs to respond effectively to disruptions, such as economic crises, supply chain disruptions, and pandemics. However, challenges such as limited digital infrastructure, skill gaps, and financial constraints hinder the full realization of these benefits. The study concludes with actionable recommendations for policymakers and SME leaders to foster digital adoption and build resilient organizations in emerging markets.